Scattered X-ray radiation algorithmic compensation procedure in the X-ray imaging as an alternative to hardware methods - Danyk, A.Y.; Sudakov, O.O. (Reports of the National Academy of Sciences of Ukraine, 2021)
Scattered X-ray radiation compensation algorithm proposed by authors is tested and compared with the most effective hardware methods: air-gap variation, anti-scatter grids. With the help of a numerical simulation, the simplicity and efficiency of the air-gap manipulation technique are shown to be contrasted by the side effects of this method: dramatic scanner and detector size increment. Typical antiscatter grid with r = 12 attenua tes scattered radiation with an efficiency of 10 meter air gap requiring 50 % more exposition and dose. The algorithmic compensation proposed by the authors provides the compensation at the level of the average hardware method but does not require an extra dose.